The Concept, Features and Forms of Civil Legal Liability - Vladimir Valentinovich Kozhevnikov (Britain International for Academic Research (BIAR-Publisher), 2023)
This scientific article discusses the concept of civil liability as a variety of legal liability, its features and forms of expression. At the same time, attention is focused on the fact that legal responsibility, including civil law, cannot be identified with protection measures.